Peran PPAT Dalam Penyelesaian Sengketa Non Litigasi Tumpang Tindih Penetapan Tanda Batas Tanah Untuk Pendaftaran Tanah Pertama Kali di Kantor Pertanahan Kabupaten Purbalingga - Wardhana, Anindita Tri (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
Land registration is a very important thing to get legal certainty regarding someone's land ownership, especially with the rampant news of land mafia cases, land grabbing, and the issue of abandoned and unregistered land will be taken by the State, which actually needs to be further deepened in its understanding about the takeover of abandoned land by the state so that it does not become a Hoax news. These issues have succeeded in making people begin to realize the importance of registering their lands, especially those they live in and do not have certificates, so that many are starting to be aware and register their land at the land office in the local district or city to ensure legal certainty regarding ownership of the land they occupy or own. However, in practice, even if someone has registered their land at the land office, problems can arise during the process. These problems vary, for example, overlapping land ownership and control, which can lead to land disputes. Efforts to resolve disputes over land boundary determination during initial registration by a Land Deed Official (PPAT), involving village/sub-district officials, are the only non-litigation approach. Therefore, these boundary determination disputes can take several rounds and over a very long period of time before the parties finally decide to bring them to litigation. If the dispute is brought to litigation, the PPAT no longer has any role or authority; instead, it must await the Court's determination or decision regarding the land boundary. Problems inevitably arise during the land registration process, often hindering registration. Therefore, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency issued Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 21 of 2020 concerning the Handling and Settlement of Land Cases.